Given differential equation: "x\\frac{dy}{dx}+y=y^2lnx"
Dividing the given equation by "x" , we get
"\\frac{dy}{dx}+\\frac{y}{x}=\\frac{y^2lnx}{x}"
Observe that the above differential equation is Bernoulli's differential equation.
It can be reduced to Linear Differential equation dividing the equation by "y^2" and then take the substitution "\\frac{1}{y}=z\\Rightarrow \\frac{1}{y^2}\\frac{dy}{dx}=-\\frac{dz}{dx}"
Then the given differential equation becomes
"\\frac{1}{y^2}\\frac{dy}{dx}+\\frac{1}{y}\\frac{1}{x}=\\frac{lnx}{x}"
"\\Rightarrow -\\frac{dz}{dx}+\\frac{z}{x}=\\frac{lnx}{x}\n\n\\Rightarrow \\frac{dz}{dx}-\\frac{z}{x}=-\\frac{lnx}{x}"
The above is a first order linear differential equation of the form
"\\frac{dz}{dx}+p(x)z=g(x)" , where "p(x)=-\\frac{1}{x}" and "g(x)=-\\frac{lnx}{x}"
General solution to the differential equation is
"z" (Integrating Factor)"=\\int" (Integrating Factor)("g(x)dx+C" , where
Integrating Factor "=e^{\\int p(x)dx}"
Using the above, we have
Integrating Factor = "=e^{\\int (-\\frac{1}{x})dx}=e^{-lnx}=e^{ln(\\frac{1}{x})}=\\frac{1}{x}"
General solution is
"z(\\frac{1}{x})=\\int (\\frac{1}{x})(-\\frac{lnx}{x})dx+C=-\\int \\frac{lnx}{x^2}dx+C"
Take the substitution "lnx=u\\Rightarrow \\frac{1}{x}dx=du" and "\\frac{1}{x}=e^{-u}"
Then, we get
"\\frac{z}{x}=-\\int (ue^{-u})du+C=-[-ue^{-u}-e^{-u}]+C" (Using integration by parts)
That is we get
"\\frac{z}{x}=[ue^{-u}+e^{-u}]+C=\\frac{lnx}{x}+\\frac{1}{x}+C" "(u=lnx)"
That is we get
"\\frac{1}{xy}=\\frac{lnx}{x}+\\frac{1}{x}+C(z=\\frac{1}{y})"
Therefore, general solution to the given differential equation is
"ylnx+y+C=1"
Comments
Leave a comment